1+2•{3+4÷[5-6÷(7-8÷(9-1))]}
Răspunsuri la întrebare
Răspuns de
3
1+2•{3+4:[5-6:(7-8:8)]}=
1+2•[3+4:(5-6:6)]=
1+2•(3+4:4)=
1+2•4=
1+8=
9
1+2•[3+4:(5-6:6)]=
1+2•(3+4:4)=
1+2•4=
1+8=
9
Răspuns de
3
1 + 2 × { 3 + 4 : [ 5 - 6 : ( 7 - 8 : ( 9 - 1 ) ] } = 9
= 1 + 2 × { 3 + 4 : [ 5 - 6 : ( 7 - 8 : 8 ) ] } =
= 1 + 2 × [ 3 + 4 : ( 5 - 6 : 6 ) ] =
= 1 + 2 × ( 3 + 4 : 4 ) =
= 1 + 2 × ( 3 + 1 ) =
= 1 + 2 × 4 =
= 1 + 8 =
= 9
Alte întrebări interesante
Matematică,
8 ani în urmă
Chimie,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă